2022
DOI: 10.1038/s41598-022-07535-3
|View full text |Cite|
|
Sign up to set email alerts
|

Symbiotic bacteria of the gall-inducing mite Fragariocoptes setiger (Eriophyoidea) and phylogenomic resolution of the eriophyoid position among Acari

Abstract: Eriophyoid mites represent a hyperdiverse, phytophagous lineage with an unclear phylogenetic position. These mites have succeeded in colonizing nearly every seed plant species, and this evolutionary success was in part due to the mites' ability to induce galls in plants. A gall is a unique niche that provides the inducer of this modification with vital resources. The exact mechanism of gall formation is still not understood, even as to whether it is endogenic (mites directly cause galls) or exogenic (symbiotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 76 publications
3
40
0
Order By: Relevance
“…The four new mitogenomes of Leipothrix spp. comprise the same constant blocks I, II, III and variable zones A,B,C ( Figure 5 ), recently defined in other published mitogenomes of Eriophyidae [ 18 , 32 , 40 , 43 , 44 , 45 ]. They share the following unique traits: (1) the trn K gene precedes the COX1 gene, (2) two tRNA genes coding leucine are located on different chains of mitochondrial DNA, (3) a cluster of tRNA genes W–V precedes the 12s rRNA gene, (4) genes 16s rRNA and COX1 flank a group of uniquely arranged genes and the control region Y–L–( CR )– NAD2 – Q–C –M–K (genes located on the negative chain are underlined).…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…The four new mitogenomes of Leipothrix spp. comprise the same constant blocks I, II, III and variable zones A,B,C ( Figure 5 ), recently defined in other published mitogenomes of Eriophyidae [ 18 , 32 , 40 , 43 , 44 , 45 ]. They share the following unique traits: (1) the trn K gene precedes the COX1 gene, (2) two tRNA genes coding leucine are located on different chains of mitochondrial DNA, (3) a cluster of tRNA genes W–V precedes the 12s rRNA gene, (4) genes 16s rRNA and COX1 flank a group of uniquely arranged genes and the control region Y–L–( CR )– NAD2 – Q–C –M–K (genes located on the negative chain are underlined).…”
Section: Resultsmentioning
confidence: 61%
“…Synapomorphic status of bifurcating setae. Based on a consensus of molecular and morphological phylogenetic analyses, there is now very strong support for a close relationship between Eriophyoidea and Nematalycidae [ 4 , 5 , 44 , 51 , 52 , 53 ]. The bifurcating form of setae in Eriophyoidea provides additional evidence for this affiliation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, Hearn et al [ 16 ] reported that they did not detect the expression of genes encoding for phytohormones in the young larvae of the gall wasp, B. pallida . In addition, in the genome of the mite, Fragariocoptes setiger (Nalepa, 1894) (Phytoptidae), which causes galls on strawberry leaves, phytohormone genes and any other genes that could have entered the mite genome from the plant as a result of horizontal transfer were not found [ 48 ]. Therefore, if there are parasite–plant pairs in which gallogenesis is induced by the endogenous phytohormones of parasitic arthropods, then there are other cases, e.g., the pairs involving the wasp B. pallida or the mite F. setiger , in which gallogenesis is initiated by a different but yet unexplained mechanism.…”
Section: Stimuli That Induce the Development Of Gallsmentioning
confidence: 99%
“…Insect-associated microorganisms could be important mediators of interactions between insects and plants ( Hammer and Bowers, 2015 ; Sugio et al., 2015 ; Wielkopolan and Jakubowska, 2021 ; Coolen et al., 2022 ). Symbiotic relationships between inducing insects and microorganisms have been hypothesised to be involved in plant gall development ( Hansen and Moran, 2014 ; Tooker and Helms, 2014 ; Gätjens-Boniche, 2019 ; Klimov et al., 2022 ). Delivery of bacteria under natural or artificial conditions by insect vectors has been reported in many insect–plant interactions ( Zeidan and Czosnek, 1994 ; Galambos et al., 2021 ; Wielkopolan and Jakubowska, 2021 ; Ratcliffe et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%